Disaster resilience of household-level food-energy-water nexus - Karan, Ebrahim; Mohammadpour, Atefeh (Frontiers in Sustainable Resource Management, 2024)
This study examines the resilience and sustainability of household-level Food-Energy-Water (FEW) systems in the face of increasing natural disasters exacerbated by climate change. With the backdrop of escalating natural hazards and heightened vulnerabilities, this research explores innovative approaches to enhancing household resilience through the implementation of sustainable FEW systems such as rainwater harvesting, sand filtration, solar energy, geothermal energy, gas-powered and solar generators, hydroponic food production, and small greenhouses. Three primary scenarios, food disruption, energy scarcity, and water shortage are analyzed to evaluate the effectiveness of various household-level FEW systems within a residential context. These systems are compared in terms of cost-effectiveness and performance, highlighting their capacity to supply essential needs during crises. The paper also introduces an integrated nexus approach, considering the interdependencies among food, energy, and water systems, and evaluates the compounded impact of simultaneous disruptions. This comprehensive analysis aims to provide actionable insights into the development of resilient infrastructures at a micro-scale, which can significantly mitigate the adverse effects of global environmental changes on local scales.